2000
DOI: 10.1183/09031936.00.15109200
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle strength and endurance in patients with mild COPD and the effects of weight training

Abstract: This study poses two questions: 1) is there an abnormality in isokinetic skeletal muscle strength and endurance in mild chronic obstructive pulmonary disease (COPD)? and 2) what is the effect of a randomized, controlled, 12 week hospital outpatient weight training programme in terms of skeletal muscle function and exercise tolerance?Upper and lower limb isokinetic maximum and sustained muscle function were compared in 43 COPD patients (age 4911 yrs), mean forced expiratory volume in one second (FEV1) 7723% pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(84 citation statements)
references
References 23 publications
8
73
0
1
Order By: Relevance
“…Similarly, a 12 week low intensity repetitious exercise of the upper and lower extremities improved endurance of individual muscles but also increased the total work performed on the treadmill. 34 These studies, like ours, show that low intensity muscle training can not only increase the strength of individual muscles, but also exercise tolerance and walking endurance. Our muscle conditioning protocol was similar but more intense than the one used by Simpson and co-workers which required 30 repetitions of knee extension and leg press during each triweekly session.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, a 12 week low intensity repetitious exercise of the upper and lower extremities improved endurance of individual muscles but also increased the total work performed on the treadmill. 34 These studies, like ours, show that low intensity muscle training can not only increase the strength of individual muscles, but also exercise tolerance and walking endurance. Our muscle conditioning protocol was similar but more intense than the one used by Simpson and co-workers which required 30 repetitions of knee extension and leg press during each triweekly session.…”
Section: Discussionsupporting
confidence: 72%
“…10 11 These training exercises have been shown to improve the functional status of these patients. [27][28][29][30][31][32][33][34] Greater improvements in cardiorespiratory fitness have been noted following high intensity training. 30 However, some patients with severe ventilatory limitation may be unable to tolerate high intensity training, especially at the outset.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the GDG reviewed eight RCTs of exercise training versus control 35–42. There were six studies composed solely of resistance training35 36 38 40–42; one study including a combination of aerobic and resistance training39; and one study including mobility training 37. All studies incorporating resistance training demonstrated an increase in muscle strength.…”
Section: Evidencementioning
confidence: 99%
“…Pre-transplant conditions such as COPD are associated with muscle weakness, which can be ameliorated with training. 40,41 Aft er transplantation, strength training can target both muscle weakness and osteoporosis, 40,41 which are secondary eff ects of immunosuppressant medications and inactivity. Muscle strength has been shown to deteriorate rapidly aft er transplant, with one study reporting a mean reduction in quadriceps force of 32% within 0.9 to 2 months following transplantation compared with pretransplant values.…”
Section: Strength Trainingmentioning
confidence: 99%
“…36 Despite the lack of evidence, the positive eff ects of exercise training in lung transplant candidates have been widely acknowledged in such pre-transplant conditions as COPD, 37 cystic fi brosis, 38 and interstitial lung disease. 39 Individuals with COPD who participate in exercise training benefi t from increased peripheral muscle strength, 40,41 improved endurance, [41][42][43][44][45] decreased dys-pnea, 44,45 a reduced number of exacerbations, 44 and enhanced quality of life. 42,45 Individuals with cystic fi brosis who participated in regular exercise experience improvements in aerobic fi tness, as demonstrated by reduced exercise ventilation and heart rate 46 and a slower decline in pulmonary function.…”
Section: Pre-transplantmentioning
confidence: 99%